The Tribe Anisoscelini (Hemiptera: Heteroptera, Coreidae) in Argentina - Coscarón, María Del Carmen; Pall, José Luis (Zootaxa, 2015)
Eight genera and 21 species of the tribe Anisoscelini (Coreidae, Coreinae) are recorded in Argentina: Anisoscelis foliaceus (Fabricius); Coribergia declivicollis (Berg); Dalmatomammurius vandoesburgi (Brailovsky); Holymenia hystrio (Fabricius); Leptoglossus chilensis (Spinola); L. cinctus (Herrich-Schaeffer); L. concolor Walker; L. crassicornis (Dallas); L. dentatus Berg; L. fasciatus (Westwood); L. gonagra (Fabricius); L. impictus (Stål); L. ingens (Mayr); L. neovexillatus Allen; L. quadricollis (Westwood); L. stigma (Herbst); L. vexillatus (Stål); L. zonatus (Dallas); Phthia lunata (Fabricius); Phthiacnemia picta (Drury) and Ugnius kermesinus (Linnaeus). A key to genera belonging to the tribe is provided. L. stigma is recorded for the first time in Argentina with new locality records for La Rioja, Salta and San Juan.